Concentration dependent rate constants of sodium substitute functionalities during wheat dough development. (February 2019) - Jekle, Mario; Necula, Andreea; Jekle, Margit; Becker, Thomas
Abstract: Chloride salts can serve as sodium chloride (NaCl) substitutes in wheat dough for sensory or technological reasons. Therefore, the effect of different substitutes on wheat dough development during mixing (optimum water absorption, dough development time, stability) and fermentation (maximum dough height) with a material-adapted water addition and mixing time were investigated. The substitutes had effects on all measures at a level of 2 g salt 100 g −1 wheat flour, with the exception of KCl. The intensity of the effect significantly followed the Hofmeister series due to an altered hydration behavior of the structure-determining gluten proteins. The experiments were supported by CLSM micrographs combined with image analysis. Next to an absolute substitution, the main focus of the study were concentration dependent functionalities of the chloride salts. Therefore, concentration dependent rate constants were calculated based on the application of different concentration levels of the chloride salts. These rate constants showed in all cases a similar tendency following the Hofmeister series. Graphical abstract: Unlabelled Image Highlights: Different chloride salts in wheat dough result in different dough functionalities. Dough development functionalities with sodium substitutes follow Hofmeister series. Concentration dependent rate constants distinguish minor components in dough. Absolute substitution & rate constants of chloride substitutes follow the same trend.